Effects of possible changes in natural gas, nuclear, and coal energy consumption on CO2 emissions: Evidence from France under Russia?s gas supply cuts by dynamic ARDL simulations approach - Kartal, Mustafa Tevfik; Pata, Ugur Korkut; Depren, Serpil Kilic; Depren, Ozer (ELSEVIER SCI LTD, 2023)
The study explores the influences of potential changes in energy consumption on carbon dioxide (CO2) emissions, focusing on disaggregated energy consumption sources. In this manner, the study considers France as the leading nuclear energy-consuming country in Europe, includes yearly data between 1970 and 2021, and performs the dynamic autoregressive distributed lag (DYNARDL) model. In addition, the Kernel-based regularized least squares (KRLS) is used for robustness check. The results reveal that (i) cointegration exists between the dis-aggregated energy consumption indicators and CO2 emissions; (ii) nuclear, natural gas, oil, and coal energy have a statistically significant effect on CO2 emissions, while renewable energy is not statistically significant; (iii) nuclear power has a decreasing effect on CO2 emissions; (iv) positive (i.e., increasing) shocks to nuclear reduce CO2 emissions, even if they are 300 % in the case of counterfactual shocks; (v) any positive (i.e., increasing) shocks to coal have a drastically increasing effect on CO2 emissions, even if they are 25 % in the case of counterfactual shocks; (vi) the KRLS approach confirms the robustness of the results. Thus, this study suggests that France should continue to rely on nuclear power for electricity generation and that French policymakers should reduce electricity exports to European Union countries to provide an alternative against the Russian natural gas shock by preventing a reduction in energy supply.
Keywords: Coal Energy Consumption; CO2 Emissions; Dynamic ARDL Simulations; Natural Gas Energy Consumption; Nuclear Energy Consumption; RENEWABLE ENERGY; ECONOMIC-GROWTH; TIME-SERIES; UNIT-ROOT; HYPOTHESIS; URBANIZATION; PIPELINE; Energy & Fuels; Engineering